Ramadan's final ten nights: a sīrah-inspired path to success - Zainan Nazri, Nurul Jannah (Human Assistance & Development International Inc. (HADI Inc.), 2026)
This article explores the significance of the final ten nights of Ramaḍān through a Sīrah-based perspective, emphasizing that true success lies in one’s spiritual ending. Drawing on the Prophetic example of intensified worship, it highlights practices such as prayer, supplication, and Qur’ān recitation, especially in seeking Laylat al-Qadr. The article concludes that these nights offer a critical opportunity for repentance, spiritual purification, and attaining divine forgiveness.